Metastasis in dedifferentiated liposarcoma: Predictors and outcome in 148 patients. Issue 7 (July 2015) - Tirumani, S.H.; Tirumani, H.; Jagannathan, J.P.; Shinagare, A.B.; Hornick, J.L.; Ramaiya, N.H.; Wagner, A.J.
Abstract Objective To describe the pattern of dedifferentiated liposarcoma (DDLPS) metastases and to analyze their predictors and outcome. Materials and methods In this retrospective study, we reviewed the imaging and clinical records of all consenting patients with histopathology-confirmed DDLPS seen from 2000 through 2012. The predictive value of clinical and histopathologic parameters for metastasis later in the disease course was analyzed using univariate and multivariate analyses. Survival of patients with and without metastasis was compared using Log-rank test. Results Records of 148 patients (57 women, 91 men; mean age 59 years, range 30–87 years) were reviewed. Distant metastases were observed in 44/148 patients (29.7%), 9/44 (20.5%) at presentation and 35/44 (79.5%) developing them later at a median interval of 8 months (IQR = 0.80–26 months). Median duration of follow-up was 38 months (IQR = 18–74 months) with 77/148 patients (31 with metastases) deceased at the time of analysis. Median survival was 28 months (IQR = 10–56 months) for patients with metastases and 38 months (IQR, 17–65 months) for patients without metastases (p = 0.0123, Log-Rank test; Hazard ratio 1.79 [95% confidence interval 1.11–2.84]). Lung was the most common site of metastases (33 patients, 22.3%). On univariate analysis, grade and local recurrence were associated with subsequent risk of metastasis where as age, tumor size, site, de novo dedifferentiation, number of previous surgical resections, margin positivity and chemoradiation were not. On multivariate analysis, high tumor grade (p-value = 0.0005, OR 5.05; 95% CI 2.01–13.48) and local recurrence (p-value = 0.0025, OR 4.46; 95% CI 1.67–13.40) predicted metastasis. Conclusion Lung was most frequent site of DDLPS metastases. Risk of developing metastatic disease was statistically associated with tumor grade and local recurrence. Metastatic disease was associated with decreased survival.